„Vi er en nation af immigranter“: Om kollektive erindringspraksisser og immigrationsmytologi i nutidens USA - Villemoes, Katinka Fjeldsø (Tidsskriftet Antropologi, 2005)
Katinka Fjeldsø Villemoes: “We Are a Nation of Immigrants”: On Collective Memory Practices, and Immigration Mythology in Contemporary United States In this article, I investigate practices of collective remembering and forgetting in the United States of America. I take as my starting point a certain period in the history of the USA, namely the extensive flows of immigrants who came to the USA in the end of the 19th and the beginning of the 20th century, and I demonstrate how this historical period is celebrated, represented and remembered in a particularly interesting manner. I argue that the romanticized tale of “the immigrants who created America” plays an important role in defining what American national identity is. The common sense representation of the immigrants who came to the USA in search of freedom and opportunity fits perfectly with today’s political and intellectual climate in the USA, because within the framework of this immigrant mythology, the individual citizen is given the opportunity to celebrate his national identity as an American, but he is also given the opportunity to celebrate his country’s ethnic, racial, cultural, and religious diversity.